Lone Star Legacy - William W. Johnstone (New York, NY Kensington Books, 2023)
Forever Texas.Johnstone Country--and how.The bestselling authors of the American West return to the wildest days of the Lone Star State, when dreams were bigger, passions bolder, and legacies forged with undaunted courage, grit, and maybe some bullets.The land is theirs. Now they have to tame it. Based on true events.South Texas, 1854. Regis Royle is determined to turn eighteen thousand acres of raw prairie into the greatest cattle ranch in the world. But he can't do it alone. The region is wilder than a herd of mustangs--and crawling with rustlers. Teaming up with the Cattlemen's Justice Consortium, Regis hopes to stop the rustling and start laying tracks for a new railway. Problem is, the cattlemen--including Jarvis "Bone" McGraw, Regis's own ranch manager--can't help but lock horns with the Texas Rangers. And it doesn't take long for this brewing pot of very bad blood to get a whole lot worse ...First blood is spilled in Corpus Christi. Regis's reckless young brother Shep is wounded by the beautiful daughter of their fiercest enemies, the powerful Valdez family. The news of a possible rail line has divided the ranchers into warring factions. And Regis Royle has to keep the peace with McGraw, take a gamble with his business partner, and keep his wayward brother in one piece. But things really heat up when Regis learns that the Valdez family are claiming rights to the Royle Ranch's land. And they'll do anything to get it back. Even kill ...The brothers Royle and their partners have the most to lose--including their lives. They made a pledge to themselves to build the greatest ranch in America. To see it through to the end, they'll have to ride hard and learn the bitter necessity of violence and bloodshed
western - adult fiction
Keywords: 1848-1860; action and adventure fiction; brothers fiction; cowboys fiction; frontier and pioneer life fiction